PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA MODEL INKUIRI TERBIMBING DENGAN STRATEGI MOTIVASI ARCS UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMP - Asnita, Asnita; Wasis, Wasis; Soetjipto, Soetjipto (Universitas Negeri Surabaya, 2016)
This research aimed to produce learning science materials using guided inquiry model with the ARCS motivational strategies that feasible to improve students? learning achievement. The development of learning materials used 4D model design and it was tested in the VII grade of SMPN 17 Kendari, even semester in academic year of 2014/2015 with One-Group Pretest-Posttest Design. The data collections used validation, observation, test, and quetionnaires methods. The data analysis techniques used qualitative descriptive analysis. The results of this research showed: 1) the developed teaching and learning materials were valid with good category; 2) learning implementation was conducted; 3) students? motivation after conducting the learning has a good category and 4) students? learning achievement has increased with high category gain score. Based on the results, it could be concluded that the guided inquiry learning models that integrate the ARCS motivational strategies were feasible to improve the learning achievement of junior high school students. Penelitian ini bertujuan untuk menghasilkan perangkat pembelajaran IPA model inkuiri terbimbing dengan strategi motivasi ARCS yang layak untuk meningkatkan hasil belajar siswa. Pengembangan perangkat pembelajaran mengikuti rancangan model 4-D dan diujicobakan di kelas VII SMPN 17 Kendari semester genap tahun ajaran 2014/2015 dengan desain One-Group Pretest-Posttest design. Pengumpulan data menggunakan metode validasi, observasi, tes, dan angket. Teknik analisis data menggunakan analisis deskriptif kualitatif. Hasil penelitian ini menunjukkan: 1) Perangkat pembelajaran yang dikembangkan valid; 2) Semua rencana pembelajaran terlaksana dengan kategori baik; 3) motivasi siswa dengan kategori baik terhadap pembelajaran; 4) hasil belajar siswa mengalami peningkatan dengan skor N-gain berkategori tinggi. Berdasarkan hasil penelitian tersebut dapat disimpulkan bahwa perangkat pembelajaran model inkuiri terbimbing dengan strategi motivasi ARCS yang dikembangkan layak untuk meningkatkan hasil belajar siswa SMP.